Medicine : prep manual for undergraduates - K George Matthew; Praveen Aggarwal (New Delhi : Elsevier, 2019)
There have been rapid advances in the field of Medicine in the last few years. This has led the authors to come out with the seventh edition of this book which is thoroughly revised to include up-to-date knowledge. As in previous editions, the question-answer format of the book has been retained. This book is the best-selling book in its segment and is 'must-have' for all the undergraduate medical students as it prepares them well for both theory and practical examinations. Additionally, it is also useful for the dentistry and nursing students. . Ex tensive revision of majority of answers to keep the students updated in their knowledge in the field of Medicine. . Preservation of text in pointwise manner with suitable figures, flowcharts, tables and boxes which will help the students in quick learning and revision.. Inclusion of evidence-based guidelines on diagnosis and management of diseases in the form of flowcharts... Management of common medical emergencies like anaphylaxis, acute myocardial infarction, acute pulmonary embolism, acute hear t failure, electrolyte imbalance, status epilepticus, upper gastrointestinal bleed, psychiatric emergencies, diabetic emergencies, poisonings, heat-related emergencies, snake bites, etc. . Emphasis has been laid on clinical presentation with relevant description of medications.
Includes index.
Keywords: General Medicine; Undergraduate medical students